蔚州 雲興寺의 佛經刊行에 관한 硏究 - 배현숙 (서지학연구, 0(44), 2009)
17세기 후반 울산 운흥사에서는 많은 불경을 간행하였다. 이 시기는 왜란과 호란이 끝나고 안정기에 접어든 시점으로 문화적인 활동을 하기 좋은 여건이 조성되었기 때문이다. 목판으로 서적을 간행하기 위해서는 판각을 위한 여건이 마련되어 있어야 한다. 우선 인적인 요소로 불경을 간행하고자 하는 발원자와 주관자, 이를 위해 경제적으로 지원하는 시주, 출판에 필요한 능숙한 기술을 보유하고 있는 기술자, 이 삼요소가 갖추어져야 한다. 또한 판각용의 판목과 인출할 종이 등 여러 물품을 쉽게 조달할 수 있어야 한다. 당시 운흥사에는 이들 조건을 모두 갖추어져 있었으므로 15종의 불경과 2종의 판화를 판각하고 인출할 수 있었다. 발원자와 주관자는 서적 권말에 수록된 경우도 있고, 발문에 수록된 경우도 있다. 다수의 서적 판각에 발원한 스님은 學薰과 演熙였다. 권말에는 시주도 밝히고 있는데, 속인과 스님을 합해 모두 59명으로 집계된다. 대표적 속인 대시주는 金士男, 李終山, 李鶴春 등이다. 이 가운데 李終山은 자신의 이름, 돌아가신 부모님의 명의로도 시주하였다. 승가의 대시주는 雪眞, 彦明, 靈寬, 天心, 太圭, 學琳 비구 등이다. 이외에도 난외에 소액을 시주한 사람들의 인명이 새겨져 있는데, 모두 1,500명에 달한다. 다양한 기술자가 동원되었는데, 대표적인 장인은 각수이다. 각수는 모두 41명 이상 동원되었다. 원담(元淡)과 연희(演熙)가 가장 능숙한 각수였다. 연희는 모두 15종 서적 판각에 참여하여 덕유산에서 목재를 구해오고, 연판하고, 판각한 각수이다. 상당수의 서적에 粧頭刻手로도 활동하였다. 운흥사의 각수들 가운데 연희(演熙), 원담(元淡), 영찬(靈贊), 이택(已擇), 평흘(平屹), 능신(能信)은 판면에 자신의 이름을 남겼기 때문에 이를 통해 그들의 판각기술을 엿볼 수 있다. 고종초 이전에 사찰은 폐사되었으나 수장하고 있던 판목은 통도사로 이관되어 현재까지 전래되고 있다. 전래되고 있는 판목은 모두 673판이다. 그러나 이들 책판은 영조 이후의 책판목록에 수록되지 않았으나 오늘의 우리는 그 판목과 인본을 통해 당시의 운흥사의 판각상황을 알 수 있게 되었다. In the late 17th century Unheung-sa in Ulsan published at its prime 15 titles of Buddhist scriptures and 2 titles of woodcut prints(illustrations of the Buddhist). In the early 19th century Unheung-sa was ruined, but no one knows exactly when, why or how. 673 woodblocks kept in Unheung-sa were relocated to Tongdo-sa. However those woodblocks were not listed on the catalogs of woodblocks compiled afterward. Prerequisites for xylography were human factors and materials. Human factors include planners, organizers, financial benefactors and technically skilled experts to publish scripts. Furthermore, many kinds of materials, including woodblocks to carve and papers to print, had to be easily supplied. In those days, Unheung-sa satisfied all those requirements. The prime organizers and planners were noted either at the end of the volumes or postscripts. Monks Haghun(학훈) and Yeonheui(연희) were the head planners of many titles. Benefactors, organizers and technical experts were also mentioned at the end of the volume. There were a total of 59 benefactors who were either laymen or monks. Among the secular benefactors, Kim Sanam(김사남), Yi Jongsan(이종산), Yi Hagchun (이학춘) were the donators of the largest amount of money. Yi Jongsan(이종산) donated not only in his own name but also in the names of the deceased parents. About 1,500 people who donated only small sums of money were also listed on the margins of books. Among technical experts, the most important were the xylographer. Among the 41 xylographers recruited, Wondam(원담) and Yeonheui(연희) were the most skilled. Yeonheui(연희) produced and participated in the engraving of 15 titles. He got the wood from Mt. Deokyu(덕유산), trimmed and engraved the text and illustrations. Six xylographers, including Yeonheui(연희), Wondam(원담), Youngchan(영찬), Yitaek(이택), Pyeongheul(평흘) and Neungsin(능신), left their names on the margins of the woodblocks so that we could infer their engraving skills. Although the woodblocks produced at Unheung-sa were not listed on the catalogs of woodblocks compiled since the reign of King Yeongjo, we can figure out the conditions of xylograph at Unheung-sa through the woodblocks and their prints currently kept at Tongdo-sa. KCI Citation Count: 9